Anisotropic Magnetic Supraparticles with a Magnetic Particle Spectroscopy Fingerprint as Indicators for Cold-Chain Breach - Müssig, Stephan; Granath, Tim; Schembri, Tim; Fidler, Florian; Haddad, Daniel; Hiller, Karl-Heinz; Wintzheimer, Susanne; Mandel, Karl (ACS Applied Nano Materials, 2019)
Magnetic particle spectroscopy (MPS) is used in this work to obtain a magnetic fingerprint signal from anisotropic supraparticles, i.e., microrods assembled from superparamagnetic iron oxide nanoparticles. Exceeding its intended purpose of nanoparticle characterization for biomedical magnetic particle imaging, it is shown that MPS is capable of resolving structural differences between the anisotropic alignment of individual nanoparticles and its isotropic counterpart. Additionally, orientation-dependent MPS signal variations of anisotropic supraparticles are identifiable. This finding enables the detection of cold-chain breaches (for instance, during delivery of a product that needs to be cooled all of the time) by recording the initial and final MPS signals of microrod samples integrated into the container of a frozen product.
CRIS-Team Scopus Importer:2020-04-02
Keywords: cold-chain breach; detectors; magnetic particle spectroscopy; magnetic particles; magnetic sensor; supraparticles

Anodes for Li-ion batteries prepared from microcrystalline silicon and enabled by binder’s chemistry and pseudo-self-healing - Foss, Carl Erik Lie; Müssig, Stephan; Svensson, Ann Mari; Vie, Preben J. S.; Ulvestad, Asbjørn; Mæhlen, Jan Petter; Koposov, Alexey Y. (Scientific Reports, 2020)
Silicon, while suffering from major degradation issues, has been recognized as a next promising material to replace currently used graphite in the anodes of Li-ion batteries. Several pathways to mitigate the capacity fading of silicon has been proposed, including optimization of the electrode composition. Within the present work we evaluated different binder formulations to improve the long-term performance of the Li-ion batteries’ anodes based on industrial grade silicon (Si) which is typically characterized by a particle sizes ranging from 100 nm to 5.5 microns. The decrease of pH in a binder formulation was found to detrimental for the cycling performance of Si due to enhanced formation of an ester-type bonding between the carboxylic group of the binder and hydroxyl group on the Si surface as well as cross-linking. Furthermore, the present work was focused on the use of the industrial grade Si with very high loading of Si material (up to 80% by weight) to better highlight the effects of the surface chemistry of Si and its influence on the performance of Si-based anodes in Li-ion batteries. The tested system allowed to establish a pseudo self-healing effect that manifests itself through the restoration of the anode capacity by approximately 25% and initiates after approximately 20 cycles. The stabilization of the capacity is attributed to self-limiting lithiation process. Such effect is closely related to SEI formation and transport properties of an electrode prepared from silicon of industrial grad

A Single Magnetic Particle with Nearly Unlimited Encoding Options - Müssig, Stephan; Reichstein, Jakob; Prieschl, Johannes; Wintzheimer, Susanne; Mandel, Karl (Small, 2021)
Communicating objects are demanded for product security and the concepts of a circular economy or the Internet of Nano Things. Smart additives in the form of particles can be the key to equip objects with the desired materials intelligence as their miniaturized size improves applicability and security. Beyond their proposed identification by optical signals, magnetic signals deriving from magnetic particles can hypothetically be used for identification but are to date only resolved roughly. Herein, a magnetic particle-based toolbox is reported, that provides more than 77 billion (77 × 109) different magnetic codes, adjustable in one single particle, that can be read out unambiguously, easily, and quickly. The key towards achieving the vast code variety is a hierarchical supraparticle design that is inspired by music: similarly to how the line-up variation of a musical ensemble yields distinguishable overtones, the variation of the supraparticle composition alters their magnetic overtones. By minimizing magnetic interactions, customizable signals are spectrally decoded by the simple method of magnetic particle spectroscopy. A large number of chemically adjustable magnetic codes and the possibility of their remote, contactless detection from within materials is a breakthrough for unexploited labeling applications and pave the way towards materials intelligence.
CRIS-Team Scopus Importer:2021-06-11
Keywords: identification; magnetic supraparticles; markers; tracers

Bulk Magnetic Properties Arise from Micron‐Sized Supraparticle Interactions and Can be Modified on the Nanoscale - Wolf, Andreas; Heinlein, Markus; Kent, Noah; Müssig, Stephan; Mandel, Karl (Small, 2025)
Magnetic supraparticles (SPs) can be employed as micron-sized particulate additives in arbitrary objects to serve as ID-tag or recorder of environmental triggers. Combined with magnetic particle spectroscopy (MPS), which enables read-out of the magnetic information in ambient conditions within seconds, magnetic SPs represent a powerful approach to equip materials with information. The encoded information relies on magnetic interactions within the SPs (intra-SP interactions) of chosen nanoparticles (NPs). However, possible magnetic interactions between SPs (inter-SP interactions), that might alter the MPS signal as well, have been neglected so far. Herein, it is elucidated that significant inter-SP interactions exist and that they can be tailored via adjustments in the SP structure, i.e., by defined adjustments of their intra-interaction as revealed by 3D-MuMax simulations and experiments in viscous fluids. Superparamagnetic iron oxide nanoparticle-based SP powders with strong inter-SP interactions exhibit significantly different MPS signals compared to their state after being incorporated into a matrix. Powders with weak inter-SP interactions (achieved by integration of non-magnetic SiO2 nanoparticles) show almost no signal change before and after incorporation. Both extremes of inter-SP interactions can be beneficial for various application scenarios and can be tailored on the nano-scale due to the interdependency of intra- and inter-SP interaction
CRIS-Team Scopus Importer:2025-03-07
Keywords: magnetic interactions; magnetic particle spectroscopy; matrix interactions; supraparticles

Colorful Luminescent Magnetic Supraparticles: Expanding the Applicability, Information Capacity, and Security of Micrometer-Scaled Identification Taggants by Dual-Spectral Encoding - Müssig, Stephan; Reichstein, Jakob; Miller, Franziska; Mandel, Karl (Small, 2022)
(Sub)micrometer-scaled identification (ID) taggants enable direct identification of arbitrary goods, thereby opening up application fields based on the possibility of tracking, tracing, and anti-counterfeiting. Due to their small dimensions, these taggants can equip in principle even the smallest subcomponents or raw materials with information. To achieve the demanded applicability, the mostly used optically encoded ID taggants must be further improved. Here, micrometer-scaled supraparticles with spectrally encoded luminescent and magnetically encoded signal characteristics are reported. They are produced in a readily customizable bottom-up fabrication procedure that enables precise adjustment of luminescent and magnetic properties on multiple hierarchy levels. The incorporation of commonly used magnetic nanoparticles and fluorescent dyes, respectively, into polymer nanocomposite particles, establishes a convenient toolbox of magnetic and luminescent building blocks. The subsequent assembly of selected building blocks in the desired ratios into supraparticles grants for all the flexibility to freely adjust both signal characteristics. The obtained spectrally resolved visible luminescent and invisible magnetic ID signatures are complementary in nature, thus expanding applicability and information security compared to recently reported optical- or magnetic-encoded taggants. Additionally, the introduced ID taggant supraparticles can significantly enhance the coding capacity. Therefore, the introduced supraparticles are considered as next-generation ID taggants.<br
Keywords: identification taggants; luminescent particles; magnetic particle spectroscopy; magnetic particles; nanoparticles; smart additives; supraparticles

Communicating Supraparticles to Enable Perceptual, Information-Providing Matter - Reichstein, Jakob; Müssig, Stephan; Wintzheimer, Susanne; Mandel, Karl (Advanced Materials, 2023)
Materials are the fundament of the physical world, whereas information and its exchange are the centerpieces of the digital world. Their fruitful synergy offers countless opportunities for realizing desired digital transformation processes in the physical world of materials. Yet, to date, a perfect connection between these worlds is missing. From the perspective, this can be achieved by overcoming the paradigm of considering materials as passive objects and turning them into perceptual, information-providing matter. This matter is capable of communicating associated digitally stored information, for example, its origin, fate, and material type as well as its intactness on demand. Herein, the concept of realizing perceptual, information-providing matter by integrating customizable (sub-)micrometer-sized communicating supraparticles (CSPs) is presented. They are assembled from individual nanoparticulate and/or (macro)molecular building blocks with spectrally differentiable signals that are either robust or stimuli-susceptible. Their combination yields functional signal characteristics that provide an identification signature and one or multiple stimuli-recorder features. This enables CSPs to communicate associated digital information on the tagged material and its encountered stimuli histories upon signal readout anywhere across its life cycle. Ultimately, CSPs link the materials and digital worlds with numerous use cases thereof, in particular fostering the transition into an age of sustainability.<br
Keywords: digitization; information; miniaturized information providers; nanoparticles; recorders; supraparticles

Customizable Induction Heating Profiles: from Tailored Colloidally Stable Nanoparticles Toward Multi-Stage Heatable Supraparticles - Luthardt, Leoni; Raczka, Theodor; Hurle, Katrin; Müssig, Stephan; Mandel, Karl (Advanced Functional Materials, 2024)

Hollow Superparamagnetic Nanoparticle-Based Microballoons for Mechanical Force Monitoring by Magnetic Particle Spectroscopy - Wintzheimer, Susanne; Müssig, Stephan; Wenderoth, Sarah; Prieschl, Johannes; Granath, Tim; Fidler, Florian; Haddad, Daniel; Mandel, Karl (ACS Applied Nano Materials, 2019)
The determination of induced mechanical forces in ball mills is an ongoing problem, which is so far mainly addressed by simulations. Herein, we suggest utilizing superparamagnetic microballoons as sensor particles for mechanical stress. The defined assembly of superparamagnetic nanoparticles yields microballoons with hollow cores, which makes them susceptible to mechanical forces. It is shown that the hollow structure is continuously fragmented under static or dynamic force application. By use of magnetic particle spectroscopy, these structural changes are readily detected and enable the quantification of the applied mechanical forces in ball mills.
CRIS-Team Scopus Importer:2020-04-02
Keywords: ball milling; magnetic particle spectroscopy; magnetic particles; sensor; supraparticles

Influence of magnetic interactions in iron oxide nanoparticle polymer composites on magnetism and induction heating - Raczka, Theodor; Wolf, Andreas; Reichstein, Jakob; Stauch, Claudia; Schug, Benedikt; Müssig, Stephan; Mandel, Karl (Journal of Magnetism and Magnetic Materials, 2024)
Induction heating of composite materials is of great interest in fields such as controlled polymer curing or degradation, self-healing or contactless joining. Ferrimagnetic iron oxide nanoparticle (IONPs) are suitable candidates for a powder additive to provide this inductive heating functionality, while being low-cost, abundant and a well-studied material class. Varying IONP size, morphology or doping facilitates fine-tuning of their heating properties. However, the interactions of such IONP additives in material composites are often neglected and can significantly alter the induction heating mechanism. In this work, we systematically vary the IONP interactions in polydimethylsiloxane composite materials by integrating 1.) dispersed IONPs 2.) supraparticles of IONPs (micrometer-assemblies), and 3.) oven-dried hard agglomerated IONPs. Additionally, these three levels of interaction are investigated for three different IONPs types (dodecahedrally and octahedrally shaped, as well as cobalt-doped). In general, dispersed IONPs reveal a broader hysteresis and therefore a faster heating curve. We highlight that not only IONP characteristics (size, morphology, doping), but also excitation field strength and foremost IONP interactions in the composite materials are parameters that are interdependent regarding induction heating and need to be considered as such for optimization in an application-oriented scenario.<br
Created from Fastlane, Scopus look-up
Keywords: Iron oxide nanoparticles; Induction heating; Magnetic interactions; Nanoparticle morphology; Micro-assemblies; Coercive field strength

Magnetic in situ determination of surface coordination motifs by utilizing the degree of particle agglomeration - Wolf, Andreas; Zink, Andreas; Stiegler, Lisa; Branscheid, Robert; Apeleo Zubiri, Benjamin; Müssig, Stephan; Peukert, Wolfgang; Walter, Johannes; Spiecker, Erdmann; Mandel, Karl (Journal of Colloid and Interface Science, 2023)
Most analytical techniques used to study the surface chemical properties of superparamagnetic iron oxide nanoparticles (SPIONs) are barely suitable for in situ investigations in liquids, where SPIONs are mostly applied for hyperthermia therapy, diagnostic biosensing, magnetic particle imaging or water purification. Magnetic particle spectroscopy (MPS) can resolve changes in magnetic interactions of SPIONs within seconds at ambient conditions. Herein, we show that by adding mono- and divalent cations to citric acid capped SPIONs, the degree of agglomeration can be utilized to study the selectivity of cations towards surface coordination motifs via MPS. A favored chelate agent, like ethylenediaminetetraacetic acid (EDTA) for divalent cations, removes cations from coordination sites on the SPION surface and causes redispersion of agglomerates. The magnetic determination thereof represents what we call a “magnetically indicated complexometric titration”. The relevance of agglomerate sizes for the MPS signal response is studied on a model system of SPIONs and the surfactant cetrimonium bromide (CTAB). Analytical ultracentrifugation (AUC) and cryogenic transmission electron microscopy (cryo-TEM) reveal that large micron-sized agglomerates are required to significantly change the MPS signal response. With this work, a fast and easy-to-use characterization method to determine surface coordination motifs of magnetic nanoparticles in optically dense media is demonstrated.
Keywords: Superparamagnetic iron oxide nanoparticles (SPIONs); Magnetic particle spectroscopy (MPS); Agglomeration; Colloidal surface chemistry; Cation coordination

Magnetic Supraparticles as Identifiers in Single-Layer Lithium-Ion Battery Pouch Cells - Deuso, Sara Li; Ziegler, Simon; Weber, Daniel; Breuer, Felix; Haddad, Daniel; Müssig, Stephan; Flegler, Andreas; Giffin, Guinevere A.; Mandel, Karl (Chemsuschem, 2024)
The development of effective recycling technologies is essential for the recovery and reuse of the raw materials required for lithium-ion batteries (LIBs). Future recycling processes depend on accessible information, necessitating the implementation of a digital battery passport. The European battery regulation mandates the use of a machine-readable identifier physically attached to the batteries for accessing digital information. Since externally applied optical labels are vulnerable to mechanical damage, technologies for identification without these restrictions could be beneficial. This study demonstrates that magnetic supraparticles (SPs) can be used for contactless identification of lithium nickel manganese cobalt oxide (NMC) battery pouch cells via magnetic particle spectroscopy (MPS) and that multiple pouch cells can be discriminated based on their specific magnetic code. A comparison of three independent model scenarios revealed that the detection of SPs and the impact on cell performance are dependent on the integration location. The results validate the concept of magnetic identification in metallic environments with MPS as an alternative to optical labeling methods. This study provides a foundation for the development of a new selective labeling and identification technology for batteries, with the potential to facilitate recycling and contribute to a more sustainable future.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Battery recycling; Digital product passport; Identification; Magnetic particle spectroscopy; Supraparticles

Magnetic Supraparticles Capable of Recording High‐Temperature Events - Wolf, Andreas; Sauer, Julian; Hurle, Katrin; Müssig, Stephan; Mandel, Karl (Advanced Functional Materials, 2024)
Superparamagnetic iron oxide nanoparticles (SPIONs) are prone to oxidation at elevated temperatures (>300 °C) and lose their magnetizability upon transition from magnetite/maghemite (γ-Fe2O3 / Fe3O4) to hematite (α-Fe2O3). Silica (SiO2) shells can effectively prevent this undesired effect up to ≈1000 °C. Herein, the study shows how to utilize SPIONs with varying SiO2 shell thickness and thus, different oxidation susceptibility, and how to combine them in micrometers sized assemblies – so-called supraparticles (SPs), to create a structurally emerging magnetic temperature recording functionality. The desired oxidation of non or weakly-protected SPIONs within SPs upon temperature events reduces dipole–dipole interactions of well-protected SPIONs in the confined SP entity. The resulting change of magnetic interactions therefore contains information on the thermal history of the SP, which can be spectrally read out via magnetic particle spectroscopy within seconds. Their working range can be tuned from 400 to 1000 °C on two independent structural hierarchy levels, namely the SiO2 shell thickness and the freely selectable ratios of different building blocks in the SP. The application of such SPs as particulate additives for magnetic recording of high-temperature events, especially relevant in metal, alloy, and ceramic processing, representing a yet unexplored and optically-independent option for bulk temperature recording is proposed.<br
Keywords: high-temperature events; magnetic particle spectroscopy; magnetic recorders; smart additives; supraparticles

Magnetizing Polymer Particles with a Solvent-Free Single Stage Process Using Superparamagnetic Iron Oxide Nanoparticles (SPION)s - Düsenberg, Björn; Groppe, Philipp; Müssig, Stephan; Schmidt, Jochen; Bück, Andreas (Polymers, 2022)
Magnetic polymer composites are used in a variety of applications in many industries. Their production methods are usually time-consuming and solvent-intensive as they are performed in liquid phase processes, such as emulsion polymerization or precipitation. In this work, a quick, easy, and solvent-free method is presented to coat polymer particles with a discrete, non-coherent coating of superparamagnetic nanoparticles. The results of the dry coating process are evaluated optically, by means of scanning electron microscopy (SEM), via powder X-ray diffraction and thermally by means of differential scanning calorimetry, before finally demonstrating the effectiveness of dry coating by means of a vibrating sample magnetometer<br

Multifunctional Polymer Composites for Automatable Induction Heating with Subsequent Temperature Verification - Reichstein, Jakob; Raczka, Theodor; Stauch, Claudia; Schug, Benedikt; Müssig, Stephan; Mandel, Karl (Advanced Engineering Materials, 2024)
Manipulating ferromagnetic particles using an alternating current (AC) magnetic field is a versatile method for quick, local, and on-demand heat generation. These particles can be incorporated into various matrices as heating elements. Their heat release can be controlled by adjusting process or material parameters. Herein, a proof-of-concept for a flexible polymer composite with customizable magnetically triggered heat release due to prior object identification via fluorescence readout is presented. The maximum temperature resulting from this process can be determined through a second fluorescence readout ex post. This novel combination of functionalities results from the synergistic interaction of inductively heatable magnetic supraparticles (SPs) and luminescent communicating SPs in one polydimethylsiloxane composite. The surface of the composite can be heated to the maximum temperatures of choice in a range between 125 and 200 °C within 2 s. Heat release and temperature verification provide spatial resolution of millimeters. The identification signature and the working range of the temperature indication functionality of the composite are customizable by exploiting its modular material design. The temperature indication functionality of the composite offers spatial resolution and ex-post readout at any point of interest, making it a versatile alternative to established optical thermometry methods.<br
Keywords: supraparticles; magnetic nanoparticle; induction heating; temperature indicators; smart additives

Optically Sensitive and Magnetically Identifiable Supraparticles as Indicators of Surface Abrasion - Wenderoth, Sarah; Müssig, Stephan; Prieschl, Johannes; Genin, Emilie; Heuzé, Karine; Fidler, Florian; Haddad, Daniel; Wintzheimer, Susanne; Mandel, Karl (Nano Letters, 2022)
Identifying and ensuring the integrity of products plays an important role in today's globalized world. Miniaturized information taggants in the packaging surface are therefore required to monitor the product itself instead of applying external labels. Ideally, multiple types of information are stored in such additives. In this work, micrometer-sized core-shell particles (supraparticles) were developed to provide material surfaces with both an identifier and a surface abrasion indication functionality. The core of the supraparticles contains iron oxide nanoparticles that allow identification of the surface with a spectral magnetic code resolved by magnetic particle spectroscopy. The fluorescent silica nanoparticles in the supraparticle shell can be abraded by mechanical stress and resolved by fluorescence spectroscopy. This provides information about the mechanical integrity of the system. The application as surfaces, that contain several types of information in one supraparticle, was demonstrated here by incorporating such bifunctional supraparticles as additives in a surface coating.
CRIS-Team Scopus Importer:2022-05-06
Keywords: abrasion indicator; identification; magnetic particle spectroscopy; supraparticles; surface coatings

Recording Temperature with Magnetic Supraparticles - Reichstein, Jakob; Müssig, Stephan; Bauer, Hannes; Wintzheimer, Susanne; Mandel, Karl (Advanced Materials, 2022)
Small-sized temperature indicator additives autonomously record temperature events via a gradual irreversible signal change. This permits, for instance, the indication of possible cold-chain breaches or failure of electronics but also curing of glues. Thus, information about the materials’ thermal history can be obtained upon signal detection at every point of interest. In this work, maximum-temperature indicators with magnetic readout based on micrometer-sized supraparticles (SPs) are introduced. The magnetic signal transduction is, by nature, independent of the materials’ optical properties. This facilitates the determination of valuable temperature information from the inside, that is, the bulk, even of dark and opaque macroscopic objects, which might differ from their surface. Compared to state-of-the-art optical temperature indicators, complementary magnetic readout characteristics ultimately expand their applicability. The conceptualized SPs are hierarchically structured assemblies of environmentally friendly, inexpensive iron oxide nanoparticles and thermoplastic polymer. Irreversible structural changes, induced by polymer softening, yield magnetic interaction changes within and between the hierarchic sub-structures, which are distinguishable and define the temperature indication mechanism. The fundamental understanding of the SPs’ working principle enables customization of the particles’ working range, response time, and sensitivity, using a toolbox-like manufacturing approach. The magnetic signal change is detected self-referenced, fast, and contactless.
CRIS-Team Scopus Importer:2022-07-08
Keywords: magnetic particle spectroscopy; magnetic recorders; smart additives; supraparticles; temperature indicators

Reversible magnetism switching of iron oxide nanoparticle dispersions by controlled agglomeration - Müssig, Stephan; Kuttich, Bjoern; Fidler, Florian; Haddad, Daniel; Wintzheimer, Susanne; Kraus, Tobias; Mandel, Karl (Nanoscale Advances, 2021)
The controlled agglomeration of superparamagnetic iron oxide nanoparticles (SPIONs) was used to rapidly switch their magnetic properties. Small-angle X-ray scattering (SAXS) and dynamic light scattering showed that tailored iron oxide nanoparticles with phase-changing organic ligand shells agglomerate at temperatures between 5 °C and 20 °C. We observed the concurrent change in magnetic properties using magnetic particle spectroscopy (MPS) with a temporal resolution on the order of seconds and found reversible switching of magnetic properties of SPIONs by changing their agglomeration state. The non-linear correlation between magnetization amplitude from MPS and agglomeration degree from SAXS data indicated that the agglomerates' size distribution affected magnetic properties. This journal is
CRIS-Team Scopus Importer:2021-06-04

Spray-Drying and Atomic Layer Deposition: Complementary Tools toward Fully Orthogonal Control of Bulk Composition and Surface Identity of Multifunctional Supraparticles - Müssig, Stephan; Koch, Vanessa; Cuadrado, Carlos Collados; Bachmann, Julien; Thommes, Matthias; Barr, Maissa; Mandel, Karl (Small Methods, 2021)
Spray-drying is a scalable process enabling one to assemble freely chosen nanoparticles into supraparticles. Atomic layer deposition (ALD) allows for controlled thin film deposition of a vast variety of materials including exotic ones that can hardly be synthesized by wet chemical methods. The properties of coated supraparticles are defined not only by the nanoparticle material chosen and the nanostructure adjusted during spray-drying but also by surface functionalities modified by ALD, if ALD is capable of modifying not only the outer surfaces but also surfaces buried inside the porous supraparticle. Simultaneously, surface accessibility in the porous supraparticles must be ensured to make use of all functionalized surfaces. In this work, iron oxide supraparticles are utilized as a model substrate as their magnetic properties enable the use of advanced magnetic characterization methods. Detailed information about the structural evolution upon individual ALD cycles of aluminium oxide, zinc oxide and titanium dioxide are thereby revealed and confirmed by gas sorption analyses. This demonstrates a powerful and versatile approach to freely designing the functionality of future materials by combination of spray-drying and ALD.
CRIS-Team Scopus Importer:2021-12-03
Keywords: atomic layer deposition; spray-drying; supraparticles

Supraparticles for Sustainability - Wintzheimer, Susanne; Reichstein, Jakob; Groppe, Philipp; Wolf, Andreas; Fett, Bastian; Zhou, Huanhuan; Pujales Paradela, Rosa; Miller, Franziska; Müssig, Stephan; Wenderoth, Sarah; Mandel, Karl (Advanced Functional Materials, 2021)
The indispensable transformation to a (more) sustainable human society on this planet heavily relies on innovative technologies and advanced materials. The merits of nanoparticles (NPs) in this context are demonstrated widely during the last decades. Yet, it is believed that the impact of particle-based nanomaterials to sustainability can be even further enhanced: taking NPs as building blocks enables the creation of more complex entities, so-called supraparticles (SPs). Due to their evolving phenomena coupling, emergence, and colocalization, SPs enable completely new material functionalities. These new functionalities in SPs can be utilized to render six fields, essential to human life as it is conceived, more sustainable. These fields, selected based on an entropy-rate-related definition of sustainability, are as follows: 1) purification technologies and 2) agricultural delivery systems secure humans “fundamental needs.” 3) Energy storage and conversion, as well as 4) catalysis enable the “basic comfort.” 5) Extending materials lifetime and 6) bringing materials back in use ensure sustaining “modern life comfort.” In this review article, a perspective is provided on why and how the properties of SPs, and not simply properties of individual NPs or conventional bulk materials, may grant attractive alternative pathways in these fields.
CRIS-Team Scopus Importer:2021-02-05
Keywords: nanomaterials; nanoparticles; supraparticles; sustainability

Supraparticles with a Magnetic Fingerprint Readable by Magnetic Particle Spectroscopy: An Alternative beyond Optical Tracers - Müssig, Stephan; Fidler, Florian; Haddad, Daniel; Hiller, Karl-Heinz; Wintzheimer, Susanne; Mandel, Karl (Advanced Materials Technologies, 2019)
Marking and identification of materials is becoming increasingly important due to complex global resource and supply chains. Luminescent particle-based markers have come to the forefront due to their small dimensions and their ability to be integrated in diverse materials. However, light-absorbing materials can hardly be marked by these particles, thus leading to insufficient recycling rates of, e.g., black plastics. In this work, microparticles with a unique magnetic fingerprint are tailored by modification of their nanoparticle building blocks. This fingerprint tailoring is achieved either by combination of magnetic building blocks with nonmagnetic ones in the supraparticles or, alternatively, by surface modification of the building blocks. An easy-to-use device, based on the principle of magnetic particle spectroscopy (MPS), is established to resolve the magnetic fingerprint information. This facilitates the employment of magnetic supraparticles as markers for product tracking and identification. As a proof of concept, it is shown that such particles enable the marking of black plastic.
CRIS-Team Scopus Importer:2020-04-02
Keywords: magnetic ID; magnetic particle spectroscopy; magnetic tags; markers; product identification

Tailoring magnetic supraparticles for object identification by magnetic particle spectroscopy - Müssig, Stephan; Fidler, F.; Haddad, D.; Hiller, K. H.; Wintzheimer, Susanne; Mandel, Karl (International Journal of Magnetic Particle Imaging, 2020)
Marking and identification of materials is becoming increasingly important due to complex global resource and supply chains. In this work, a miniaturized magnetic marking technology based on so-called supraparticles is presented. The hierarchical buildup of these microparticles, which are assembled from nanoparticles, allows to precisely tailor their structure. Superparamagnetic iron oxide nanoparticles as building blocks are used in this work. By surface modification and mixing them with silica nanoparticles, respectively, the supraparticle structure is varied. It is demonstrated that these structural modifications are readily detected by magnetic particle spectroscopy (MPS). Thereby, various distinguishable magnetic signals are feasible, which are even detected after incorporation into dark plastic. The presented magnetic marking technology thus proves its potential as an alternative marking technology to optical labels.
CRIS-Team Scopus Importer:2020-11-20

Towards core-shell bifunctional catalyst particles for aqueous metal-air batteries: NiFe-layered double hydroxide nanoparticle coatings on gamma-MnO2 microparticles - Flegler, Andreas; Muessig, Stephan; Prieschl, Johannes; Mandel, Karl; Sextl, Gerhard (Electrochimica Acta, 2017)
Herein, we investigated the synthesis of a bifunctional catalyst particle system for aqueous metal-air batteries. To target a system which possesses both, oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) capabilities, gamma-MnO2 microparticles were combined with NiFe layered double hydroxides (LDH) to a core-shell system. NiFe-LDH can be optimized in its constituency to yield a very low onset potential (at 10 mA cm (2)) for the oxygen evolution reaction of only 569 mV vs. Hg/HgO. We investigated different coating processes (in-situ precipitation coating and sonochemical assisted coating) in order to create a bifunctional system of LDH shell@gamma-MnO2 core. It was found that the overall catalytic functionality of the bifunctional system strongly depends on the coating process, as this ultimately determines the surface nature and thus the behavior in ORR and OER reactions, respectively, of this core-shell system. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: NiFe LDH; layered double hydroxides; metal-air batteries; OER; bifunctional catalyst